Sinergi Norma dalam Organisasi sebagai Pilar Kepemimpinan yang Efektif - Avini Nurazhimah Arfa; Tuty Kuniawaty Saragih; Henny Suharyati (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to examine the influence of organizational norm synergy on leadership effectiveness in vocational schools, specifically at SMK Atlantis Plus Depok. A qualitative descriptive approach was used, collecting data through open-ended questionnaires administered to 30 teacher respondents. Findings indicate that effective leadership is considered a key factor in shaping school norms, with the majority agreeing or strongly agreeing. Furthermore, the principal is perceived to consistently uphold organizational values through daily actions. However, existing norms have yet to sufficiently foster collaboration between students and teachers. While leadership is generally strong, improvements are needed in designing norms that promote a collaborative culture. The study recommends strategies such as developing a collaboration code of ethics, implementing ongoing leadership training, and using digital platforms to enhance communication. These findings are expected to contribute to the development of norm-based leadership models in the field of education.